Spending on Political Staffers and the Revealed Preferences of Cabinet: Examining a New Data Source on Federal Political Staff in Canada. Issue 3 (12th February 2016) - Robson, Jennifer
Abstract: There is no unifying theory to guide the study of partisan political staff. The literature suggests staffers may be variously mechanisms for resolving principal-agent problems, extensions of centralized political control or spoils given as rewards inside the core executive. Annual Public Accounts data, available only since 2007, offer a promising new addition to the debate over federal exempt staffs. This paper presents descriptive and linear regression results on staffing expenditures for five years of federal data in Canada. Using the construct of "revealed preference, " predictors of variance in ministerial spending on staffing may provide new, objective information on their function in Canadian government. Results of this study demonstrate that quantitative methods can be applied to the study of political staff and may be a helpful addition as the field continues to develop, test and refine theory. Résumé: Il n'existe pas de concept unificateur pour guider l'étude du personnel politique partisan. La littérature didactique indique que les adjoints de ministre peuvent être soit des aides servant à résoudre des problèmes de leur supérieur, soit les mandataires d'un système de contrôle politique centralisé ou même les bénéficiaires de faveurs du régime au pouvoir. Les données annuelles des comptes publics, disponibles seulement depuis 2007, constituent une nouvelle source prometteuse de données pour le débat sur le personnel exonéré fédéral. Cet article présente les résultats d'une analyse de régression descriptive et linéaire sur les dépenses de dotation en personnel au niveau fédéral canadien, sur une période de cinq ans. En utilisant la méthode des « préférences révélées », les variables explicatives dans les dépenses en dotation du personnel politique pourraient révéler des informations objectives nouvelles sur leur fonction au sein du gouvernement canadien. Les résultats de cette étude démontrent qu'on peut appliquer des méthodes quantitatives à l'étude du personnel politique et que de telles méthodes pourraient s'avérer prometteuses à mesure que l'on continue à en développer, tester et affiner la théorie.